The Impact of The Digital Story in the Development of some Life Skills among Children with Autism in A Human Development Center in Al-Qassim - Meznan, Faten Marzouq (Journal of Educational and Psychological Sciences, 2025)
The aim of the research is to identify the impact of the digital story on developing some life skills for autistic children at the Human Development Center in Buraidah Al-Qassim, and to achieve this; A list of appropriate life skills for autistic children was built, and its number (12) sub-skills distributed on three basic skills: (washing hands, eating with a spoon, wearing clothes), and the quasi-experimental approach was used. For the TEATCH program, the beginner section, and their IQ ranges from 51 to 70 according to the CARS scale and average autism according to the Gilliam scale), The measurement tool was a performance test and an accompanying note card that were applied to the research sample before, and then re-applied after the research sample was subjected to experimental treatment. Post-application, and the research recommended the necessity of circulating digital stories to day and evening care centers for people with special needs to benefit from them in developing life skills.